Performance of five D-dimer assays for the exclusion of symptomatic distal leg vein thrombosis - Luxembourg, Beate; Schwonberg, Jan; Hecking, Carola; Schindewolf, Marc; Zgouras, Dimitrios; Lehmeyer, Susanne; Lindhoff-Last, Edelgard (Thrombosis and Haemostasis, 2012)
The diagnostic value of D-dimer (DD) in the exclusion of proximal deep-vein thrombosis (DVT) is well-established but is less well-known in the exclusion of distal (infrapopliteal) DVT. Therefore, we evaluated the diagnostic abilities of five DD assays (Vidas-DD, Liatest-DD, HemosIL-DD, HemosIL-DDHS, Innovance-DD) for excluding symptomatic proximal and distal leg DVT. A total of 243 outpatients whose symptoms were suggestive of DVT received complete compression ultrasonography (cCUS) of the symptomatic leg(s). The clinical probability of DVT (PTP) was assessed by Wells score. Thirty-eight proximal and 31 distal DVTs (17 tibial/fibular DVTs, 14 muscle DVTs) were diagnosed by cCUS. Although all assays showed high sensitivity for proximal DVT (range 97–100%), the sensitivity was poor for distal DVT (range 78–93%). None of the assays were individually able to rule out all DVTs as a stand-alone test (negative predictive value [NPV] 91–96%). However, a negative DD test result combined with a low PTP exhibited a NPV of 100% for all DVTs (including proximal, tibial/fibular, and muscle DVTs) with the HemosIL-DDHS and Innovance-DD. All proximal and tibial/fibular DVTs, but not all muscle DVTs, could be ruled out with this strategy using the Liatest-DD and Vidas-DD. The HemosIL-DD could not exclude distal leg DVT, even in combination with a low PTP. The combination of a negative DD with a low PTP showed a specificity of 32–35% for all DVTs. In conclusion, our study shows that when used in conjunction with a low PTP some DD assays are useful tools for the exclusion of distal leg DVT.
Keywords: D-dimer; deep-vein thrombosis; venous thrombosis; calf vein thrombosis; compression ultrasonography